2012
DOI: 10.1103/physrevlett.108.182002
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Inference of the Resonance Content ofp(γ,K+)Λ

Abstract: A Bayesian analysis of the world's p(γ, K + )Λ data is presented. From the proposed selection of 11 resonances, we find that the following nucleon resonances have the highest probability of contributing to the reaction: S11(1535), S11(1650), F15(1680), P13(1720), D13(1900), P13(1900), P11(1900), and F15(2000). We adopt a Regge-plus-resonance framework featuring consistent couplings for nucleon resonances up to spin J = 5/2. We evaluate all possible combinations of 11 candidate resonances. The best model is se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 53 publications
5
87
0
Order By: Relevance
“…We have also compared our resonance configuration with that used by the Ghent group [17] and found that our configuration is consistent up to spin 5/2 resonances. The omission of spin 5/2 resonances in our model was discussed in Ref.…”
mentioning
confidence: 99%
“…We have also compared our resonance configuration with that used by the Ghent group [17] and found that our configuration is consistent up to spin 5/2 resonances. The omission of spin 5/2 resonances in our model was discussed in Ref.…”
mentioning
confidence: 99%
“…The interest in this state has increased since it was shown in [32] that this state was an ideal candidate to explain the peak around 1920 MeV observed in the γp → K + Λ reaction. It has been quite rewarding to see that in a recent work using Bayesian statistics to determine the most probable combinations of resonances needed to describe the γp → K + Λ reaction [33,34], a N * , J P = 1/2 + state with mass around 1900 MeV is needed to best explain the data.…”
Section: Three Body Systems Involving Kaonsmentioning
confidence: 99%
“…Yet, the atoms studied in these former works correspond to orbits with l equal or bigger than one, and one can rightly ask where are the states with l = 0. The answer to this problem was given in [3] where it was found that, based on potentials derived from chiral unitary theory [4], those states are deeply bound, by [30][31][32][33][34][35][36][37][38][39][40] MeV, but the width is about 100 MeV, which sets clear limits to their experimental observability. One must also quote that there are different claims, with larger bindings and narrower widths, based on phenomenological potentials fitted to data of kaonic atoms [1].…”
Section: Introductionmentioning
confidence: 99%
“…In a new version of the RPR model (referred to as RPR-2011) [37], several changes relative to the previous model version (referred to as RPR-2007) [27] Neither version of the model has been constrained by fits to any of the electroproduction data.…”
Section: Regge Plus Resonance Modelmentioning
confidence: 99%